Legal Sector Reform Pursuits in Ethiopia: Gaps in Grassroots Empowerment - Stebek, EN (Mizan law review, 2016)
The initial phase of Ethiopia’s Justice System Reform Program (which includes legal sector reform and judicial reform) was very ambitious with exemplary levels of zeal, budgetary allocation and commitment. This seems to have been followed by the fragmentation of reform efforts in the midst of inadequate grassroots empowerment (in decision making and resource management) while at the same time the legal sector espoused comparably similar aspirations.  There is thus the need for distinct institution-level reform tasks and empowerment in legislative drafting, law enforcement, legal education (including research and training) and access to justice. The reinvigoration of legal sector reform in Ethiopia envisages merit-based recruitment and promotion accompanied by grassroots empowerment in decision making and resource management in the context of adequate harmonization among organs and institutions of the sector. It also envisages broad-based participation including enhanced involvement of civil society organizations.  This article briefly examines the level of attention given to and the gaps in reform pursuits in lawmaking, law enforcement, legal education and access to justice. Key terms: Lawmaking, law enforcement, legal education, access to justice, legal information, the Bar, legal aid, civil societies, Ethiopia